STATUS KONSORSIUM MIKROBA LOKAL PENDEGRADASI MINYAK - Komarawidjaja, Wage; Lysiastuti, Esi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Laboratory observation were conducted to study the effect of media containing oil spillon microbial ability in utilizing oil spill as carbon sources. Microbial consortia which wasisolated from Cepu oil spill sample was inoculated on the Bushnell-Haas (BH) mediacontaining 5% Cepu crude oil.The experiment proved that microbes could be able utilizing oil as carbon source fortheir cell multiplication, the more the turbidity concentration increase, the more themicrobial population rise. Concentration of oil dissolved trend and availability that wasmeasured show a microbial surfactant generation. Furthermore, microbial density thatwas measured along experiment period indicate an increase in density.The result indicate that remediation of oil spill study which is utilizing indigenous microbesas in situ bioremediation technologies can be implemented.